The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1051/epjpv/2013019
|View full text |Cite
|
Sign up to set email alerts
|

Laser annealing of thin film polycrystalline silicon solar cell

Abstract: Performances of thin film polycrystalline silicon solar cell grown on glass substrate, using solid phase crystallization of amorphous silicon can be limited by low dopant activation and high density of defects. Here, we investigate line shaped laser induced thermal annealing to passivate some of these defects in the sub-melt regime. Effect of laser power and scan speed on the open circuit voltage of the polysilicon solar cells is reported. The processing temperature was measured by thermal imaging camera. Enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The main target of the present work, the demonstration that D-H interdiffusion can be used for precise measurement of H diffusion length and temperature in the laser spot in (a-Si:H based) multilayer films on glass, is not affected by this inhomogeneity. Irradiation with higher homogeneity is achievable by, e.g., multiple scans with a circular Gaussian intensity profile, scans with flat-top (top hat) intensity profiles, 31 scans with line lasers, 21 or applying conventional RTP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main target of the present work, the demonstration that D-H interdiffusion can be used for precise measurement of H diffusion length and temperature in the laser spot in (a-Si:H based) multilayer films on glass, is not affected by this inhomogeneity. Irradiation with higher homogeneity is achievable by, e.g., multiple scans with a circular Gaussian intensity profile, scans with flat-top (top hat) intensity profiles, 31 scans with line lasers, 21 or applying conventional RTP.…”
Section: Methodsmentioning
confidence: 99%
“…5,14,16,17 In these experiments, however, the decrease in H concentration overlapped with the increase in crystallinity so that no a-Si:H with reduced H concentration was identified. With regard to defect reduction/device improvement by laser annealing, only a few reports have been published like studies by Lee et al 20 and Chowdhury et al 21 who indeed found improvement of amorphous and polycrystalline silicon based devices by laser treatment. One reason for the limited application may be the lack of knowledge of the precise temperature as in practice the absolute temperature for RTP is often unknown 22 and the effort to measure the RTP temperature accurately by conventional methods (like thermal imaging camera, 21 pyrometer, 23 or thermocouple 24 ) is clearly high.…”
Section: Introductionmentioning
confidence: 99%
“…13,20,22 Moreover, the defects and deformations of the substrates can be avoided or lowered and the choice of substrates and IDLs (buffer layers) can be diversified. 12,16,19,21,23,24 The LC method for crystallization of a-Si thin films was studied with CW diode lasers with a line-focus in which the axis of the line-focus was perpendicular to scan directions. 24,25 Most of the past work was carried out using CW infrared (IR) lasers, and a-Si films on glass substrates were kept at elevated temperatures during the laser annealing process because at room temperature the a-Si layers exhibit low absorption of the infrared irradiation in comparison to the visible.…”
Section: Introductionmentioning
confidence: 99%
“…12,16,19,21,23,24 The LC method for crystallization of a-Si thin films was studied with CW diode lasers with a line-focus in which the axis of the line-focus was perpendicular to scan directions. 24,25 Most of the past work was carried out using CW infrared (IR) lasers, and a-Si films on glass substrates were kept at elevated temperatures during the laser annealing process because at room temperature the a-Si layers exhibit low absorption of the infrared irradiation in comparison to the visible. 5,24 To increase the light absorption, the samples were kept at temperatures in the range of 400–700 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation